Core strength and respiratory and aerodynamic vocal measurements of popular singers: clinical trial (Research, Society and Development, 2020)
Objective: to investigate the effect of an intensive physical therapy training of the core strength on respiratory and aerodynamic vocal measurements of popular professional singers. Methods: Randomized clinical trial. Sample composed of popular professional singers, eight in the control group and eight in the study group, who underwent the physiotherapeutic protocol. The measurements of maximum phonation time, sound pressure level and dynamic extension were under the responsibility of Speech Therapy professionals and the measurements of forced vital capacity, activation of the transverse abdomen muscle, and maximum respiratory pressures were under the responsibility of Physiotherapy professionals. The results were compared in the pre and post intensive physical therapy training. Results: In the treated group, there was a significant improvement in forced vital capacity, sound pressure level, activation of the transverse abdomen muscle, and maximum phonation time of /e/ voiceless. Conclusion: The intensive physical therapy training of the core strength caused an improvement in respiratory and aerodynamic vocal measurements of popular professional singers.